XXX Russian-Polish-Slovak Seminar Theoretical Foundation of Civil Engineering (RSP 2021) Selected Papers - Akimov, Pavel; Vatin, Nikolai; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book gathers the latest advances, innovations, and applications in the field of civil, environmental and construction engineering, as presented by researchers and engineers at the XXX Annual Russian-Polish-Slovak Seminar Theoretical Foundation of Civil Engineering (RSP), held in September 2021. Co-organized by six universities from Russia, Poland and Slovakia, the event covered diverse topics such as structural mechanics; building structures; geodesy and geotechnics; transport and environmental issues in civil engineering. The contributions, which were selected by means of a rigorous international peer-review process, highlight numerous exciting ideas that will spur novel research directions and foster multidisciplinary collaborations.
Chapter 1: Dynamic actions of a two-layer freely supported beam -- Chapter 2: Models of deformation of plates with double anisotropy -- Chapter 3: Parametric Study of Saw-cut Method -- Chapter 4: On the calculation of thin shells beyond the elastic limit -- Chapter 5: Homogenization in the problem of long-term loading of a layered elastic-creeping composite -- Chapter 6: Influence of the connectedness of thermoelastic fields on the stress-strain state of a circular rigidly fixed plate -- Chapter 7: Adhesive problem in the mechanics of materials -- Chapter 8: Asymptotic solution of elasticity problem in the vicinity of irregular boundary point -- Chapter 9:Mathematical modeling of the collapse form of the borehole walls.
Keywords: Buildings -- Design and construction; Geotechnical engineering; Transportation engineering; Traffic engineering; Building materials; Building Construction and Design; Geotechnical Engineering and Applied Earth Sciences; Transportation Technology and Traffic Engineering; Structural Materials; Civil engineering -- Congresses